Protective Role of Genistein in Acute Liver Damage Induced by Carbon Tetrachloride - Nalan Kuzu; Kerem Metin; Adile Ferda Dagli; Fatih Akdemir; Cemal Orhan; Mehmet Yalniz; Ibrahim Hanifi Ozercan; Kazim Sahin; Ibrahim Halil Bahcecioglu (Mediators of Inflammation)
Aim. In the present study, we investigated the protective effect of genistein in experimental acute liver damage induced by CCl4. Method. Forty rats were equally allocated to 5 groups. The first group was designated as the control group (group 1). The second group was injected with intraperitoneal CCl4 for 3 days (group 2). The third group was injected with subcutaneous 1 mg/kg genistein for 4 days starting one day before CCl4 injection. The fourth group was injected with intraperitoneal CCl4 for 7 days. The fifth group was injected with subcutaneous 1 mg/kg genistein for 8 days starting one day before CCl4 injection. Plasma and liver tissue malondialdehyde (MDA) and liver glutathione levels, as well as AST and ALT levels were studied. A histopathological examination was conducted. Results. Liver tissue MDA levels were found significantly lower in group 3, in comparison to group 2 (P<.05). Liver tissue MDA level in group 5 was significantly lower than that in group 4 (P<.001). Liver tissue glutathione levels were higher in group 5 and 3, relative to groups 4 and 2, respectively (P>.05 for each). Inflammation and focal necrosis decreased in group 3, in comparison to group 2 (P<.001 for each). Inflammation and focal necrosis in group 5 was lower than that in group 4 (P<.001). Actin expression decreased significantly in group 5, relative to group 4 (P<.05). Conclusion. Genistein has anti-inflammatory and antinecrotic effects on experimental liver damage caused by CCl4. Genistein reduces liver damage by preventing lipid peroxidation and strengthening antioxidant systems.